Financiamento de pequenas Empresas de Base Tecnológica no estado de São Paulo: estudo de caso com empresas do CIETEC - Alcântara, Daiane Ramon de (2009)
The purpose of this dissertation is to investigate the greatest financial barriers faced by Small Technology - Based Firms of CIETEC in Sao Paulo. In particular, this work aims to analyze which of these derives from the absence of adequate sources of funding. In order to achieve this objective we opted for an empirical study with a group of residents and graduated enterprises at the Incubator Center for Technological Companies from USP São Paulo. Mobilizing resources for Small Technology - Based Firms includes the study of financial environment, the institutional arrangements and mechanisms for state action and the actors in the credit and capital market. Additionally, the determinants of funding supply and demand must be understood considering the distinguishing features of this type of company. When we consider these aspects it is possible to find certain facilitator factors, such as the center infrastructure and the capabilities of entrepreneurs. Among the obstacles are mainly the products and services nature and maturation cycles and the academic profile of the founding partners. The conclusion is that the Small Technology - Based Firms of CIETEC even though with difficulties are able to do a better quest for public funding when compared to private ones made in credit and capital markets - particularly in the seed and venture capital modalities. The intense usage of public funds by these companies is sometimes a discouraging factor for market entrance, since these companies are used to survive with public funds. It seems to be a common fear among companies to have their projects rejected in the context of some agencies. In fact, when it occurs, they are obligated to stop the research and development of products and services, slowing the development process. In the field research with investors we found two possible solutions to the problem: i) the free providing, by CIETEC, of a TBCs management course in the same structure of the course made by Fundação Dom Cabral, Belo Horizonte, MG, ii) the development of tools for supporting the preparation of projects, such as courses or consultancy, to promote the reduction of mistakes made by companies during the preparation of funding requests for technology projects